Respon Struktur Portal Baja Akibat Beban Gempa Dengan Analisis Riwayat Waktu Nonlinier - Syauqi, Muhammad; Suryanita, Reni; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Earthquakes are dynamic loads that greatly affect the state of the building structure. If the strength of the building can not withstand the dynamic load, then the building will be damaged even will collapse. The purpose of this study was to identify the structural response in the Indonesian quake region by using nonlinear dynamic analysis. Structural modeling using Banda Aceh, Bengkulu and Pekanbaru earthquake locations with medium soil condition on a 10-storey building made of steel with a constant inter-floor height of 4 m. Time history analysis in earthquake plan using 3 accelerated earthquake accelerator, namely: Kobe, Imperial Valley and Chichi earthquake. Each earthquake accelerator was given three treatments: 1). The earthquake scale is decreased by 50% (0.5 g), 2). Normal earthquake scale (1 g), and 3). The scale of the earthquake is increased by 200% (2 g). The analysis results show that the displacement, velocity, and acceleration of earthquake-load structures in each region are directly proportional to the increasing or decreasing of the earthquake-scale in buildings that do not occur in plastic joints.Keywords : steel portal structure, response, displacement, velocity, acceleration, time history analysis